Cohesión familiar y la diferenciación del Sí-Mismo en adolecentes de la Unidad Educativa "Juan de Velasco", período enero - junio 2016 - Rubio Andrade, Jhosselin Nicole (2016)
The research was developed at Unidad Educativa "Juan de Velasco" the Riobamba city, during the period January-June 2016; the work was conducted with the students of first bachelors of high school parallel "C", with a population of 53 students and the nonrandom sample of 17 students and that all add 3 family members for each student, In total get 51 members of the family, the same that was chosen by the researchers using the criteria for inclusion and exclusion. The research was conducted under the scientific method, quantitative and not experimental, the research was traversal and the field, and levels was descriptive and exploratory. The data collection instruments used were: Inventory Differentiation of Self and Frienlander Skowron and the Family Cohesion Scale (Faces II) by David Olson and colleagues, to meet the different levels of differentiation, self and levels of family cohesion. Techniques for analyzing the results were processed by basic statistics in the Excel program and the results were represented through charts and graphs, later draw up the conclusions and recommendations. At the end of the investigation it was found the hypothesis, the results concern that adolescents with medium and low levels of Differentiation of Self, belonged to families with levels Dispersed and bonded family cohesion, so it is concluded that the Cohesion if family influences the formation of Differentiation of Self. Based on the results of the investigation, it was possible to design a psychoeducational Guide to report on the Family Cohesion and turn on the Differentiation of Self directed to students, families, authorities and teachers which is delivered At Unidad Educativa "Juan de Velasco" for future improvement DECE.